Two cases of visceral leishmaniasis in Colombia resistant to meglumine antimonial treatment (2009)
ABSTRACT: Visceral leishmaniasis (VL) affects over 500 000 people worldwide each year. The disease occurs in the Mediterranean basin, Central and South America and is caused by Leishmania infantum (syn L. chagasi). VL is an endemic disease in Colombia, particularly along the Caribbean coast and the Magdalena River Valley and 90% of VL cases occur in children under the age of five. The first line of treatment is chemotherapy with pentavalent antimonial compounds, including sodium stibogluconate (Pentostam®) and meglumine antimoniate (Glucantime®). These compounds are the ones most used in Colombia, at a dose of 20 mg/kg/day for 28 days. Nevertheless resistance of L. infantum to pentavalent antimonials is becoming an important problem. No cases of VL resistant to pentavalent antimonial compounds have previously been reported from Colombia. This report describes the two cases of VL resistance to antimonial compounds in a girl and a boy who did not respond to previous treatment with Pentacarinat® and Glucantime® regimens but were treated successfully with liposomal amphotericin B. Based on our findings, we recommend liposomal amphotericin B as the first line of treatment for VL due to its low toxicity, shorter administration period and the low price obtained by WHO.